Molecular Characterization and Expression Profile Analysis of Heat Shock Transcription Factors in Mungbean - Li, Shuai; Wang, Runhao; Jin, Hanqi; Ding, Yanhua; Cai, Chunmei (Frontiers in Genetics, 2019)
Heat shock transcription factors (Hsfs) are essential elements in plant signal transduction pathways that mediate gene expression in response to various abiotic stresses. Mungbean (Vigna radiata) is an important crop worldwide. The emergence of a genome database now allows for functional analysis of mungbean genes. In this study, we dissect the mungbean Hsfs using genome-wide identification and expression profiles. We characterized a total of 24 VrHsf genes and classified them into three groups (A, B and C) based on their phylogeny and conserved domain structures. All VrHsf genes exhibit highly conserved exon-intron organization, with two exons and one intron. In addition, all VrHsf proteins contain 16 distinct motifs. Chromosome location analysis revealed that VrHsf genes are located on 8 of the 11 mungbean chromosomes, and that seven duplicated gene pairs had formed among them. Moreover, transcription patterns of VrHsf genes varied in different tissues, indicating their different roles in plant growth and development. We identified multiple stress related cis-elements in VrHsf promoter regions 2 kb upstream of the translation initiation codons, and the expression of most VrHsf genes was altered under different stress conditions, suggesting their potential functions in stress resistance pathways. These molecular characterization and expression profile analyses of VrHsf genes provide essential information for further function investigation.